IL-1β directly suppress ghrelin mRNA expression in ghrelin-producing cells. (15th May 2017) - Bando, Mika; Iwakura, Hiroshi; Ueda, Yoko; Ariyasu, Hiroyuki; Inaba, Hidefumi; Furukawa, Yasushi; Furuta, Hiroto; Nishi, Masahiro; Akamizu, Takashi
Abstract: In animal models, ghrelin production is suppressed by LPS administration. To elucidate the detailed molecular mechanisms involved in the phenomenon, we investigated the effects of LPS and LPS-inducible cytokines, including TNF-α, IL-1β, and IL-6, on the expression of ghrelin in the ghrelin-producing cell line MGN3-1. These cells expressed IL-1R, and IL-1β significantly suppressed ghrelin mRNA levels. The suppressive effects of IL-1β were attenuated by knockdown of IKKβ, suggesting the involvement of the NF-κB pathway. These results suggested that IL-1β is a major regulator of ghrelin expression during inflammatory processes. Highlights: IL-1β significantly suppresses ghrelin mRNA levels in MGN3-1 cells. Ghrelin-producing cells express IL-1R. The NF-κB pathway is involved in IL-1β–induced suppression of ghrelin.